2003
DOI: 10.1200/jco.2003.11.137
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Liver Transplantation in Patients With Hepatocellular Carcinoma in the United States Between 1988 and 2001: 5-Year Survival Has Improved Significantly With Time

Abstract: Five-year survival of patients transplanted for HCC is excellent, with a steady improvement in survival over the past decade. It is possible that the published criteria for patient selection may have contributed to the better outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
143
0
5

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(154 citation statements)
references
References 32 publications
6
143
0
5
Order By: Relevance
“…These rates reflect significant improvement over earlier results, most prominently due to a more judicious patient selection based on defined HCC criteria. 45 Such favorable dropout, recurrence, and survival rates were observed despite the inclusion of 10 patients whose tumor burden surpassed the Milan criteria. In fact, 9 of the 10 patients were successfully bridged to transplantation.…”
Section: Discussionmentioning
confidence: 94%
“…These rates reflect significant improvement over earlier results, most prominently due to a more judicious patient selection based on defined HCC criteria. 45 Such favorable dropout, recurrence, and survival rates were observed despite the inclusion of 10 patients whose tumor burden surpassed the Milan criteria. In fact, 9 of the 10 patients were successfully bridged to transplantation.…”
Section: Discussionmentioning
confidence: 94%
“…However, other noncomparative studies have reported that the 5-year survival rates of HCC patients have improved with time, and these improvements started with the implementation of the MC in the clinical practice. 103 …”
Section: And Nontumor Indicationsmentioning
confidence: 99%
“…1 We present an unusual case of an LT recipient with gradually rising alpha-fetoprotein (AFP) levels who was eventually diagnosed with metastatic HCC to the right ventricle.…”
Section: To the Editorsmentioning
confidence: 99%
“…1 We present an unusual case of an LT recipient with gradually rising alpha-fetoprotein (AFP) levels who was eventually diagnosed with metastatic HCC to the right ventricle.A 57-year-old man with hepatitis C cirrhosis underwent chemoembolization for a 2.0-cm HCC lesion and then deceased donor LT in 2004. His AFP level at the time of LT was 610 ng/mL, and the explant showed 3 lesions (all < 2 cm) with microvascular invasion.…”
mentioning
confidence: 99%